Neurophysiological characteristics of reward processing in deaf college students under different social contexts - Xue Du; Ting Huang; Shiqiong Wu; Xingru Wang; Xiaoyi Chen (Frontiers in Neuroscience)
BackgroundIn the context of social exclusion, individuals tend to make choices that are advantageous to themselves and optimize their interests. Due to hearing impairment, deaf college students face more social exclusion in our society. However, the neural mechanisms of reward processing in deaf college students during different situations of social exclusion remain unknown.MethodsA total of 27 deaf college students completed the monetary and social reward delay tasks while recording event-related potential (ERP) data.ResultsThe behavioral hit rate was sensitive to the main effect of social context; that is, the deaf college students showed a higher hit rate in social inclusion than in social exclusion. The amplitude of Cue P3 elicited by reward cues was found to be higher in social exclusion than in social inclusion, particularly when the amplitudes of monetary cues were higher than those of social cues. In the reward feedback outcome phase, small magnitude induced a greater feedback-evoked P3 than large magnitude. Additionally, they exhibited a large feedback-related negativity amplitude for large-magnitude (but not for small-magnitude) monetary reward cues.ConclusionDeaf college students were more sensitive to reward cues in social exclusion than in social inclusion, especially to monetary cues, and more concerned with attaining greater monetary gains.